2019
DOI: 10.1177/0260106019830844
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism genetic risk score interacts with the Brazilian Healthy Eating Index Revised and its components to influence the odds for dyslipidemia in a cross-sectional population-based survey in Brazil

Abstract: Background: Dyslipidemia can be influenced by genetic and dietary risk factors. Aim: This study set out to investigate diet and genetic variations in Brazilian people in a cross-sectional population-based survey and to analyze the relationship between single nucleotide polymorphisms (SNPs) of genes involved in lipid metabolism and cardiometabolic-related phenotypes using a genetic risk score (GRS). Methods: We recruited 228 adults (mean age 36.5 years) who participated in the Health Survey of São Paulo (HS-SP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Furthermore, a cross-sectional study of 228 Brazilian participants from the Health Survey of São Paulo (HS-SP) ( 64 ) observed significant interactions between a GRS based on seven SNPs ( Table 1 ) and the Brazilian Healthy Eating Index Revised (BHEI-R) on the risk of dyslipidaemia. Participants with a higher GRS (5–8) had a lower odds ratio for dyslipidaemia with an intake of BHEI-R oil component above the median ( P interaction = 0.019); while those with a GRS > 9 had a lower odds ratio for dyslipidaemia with an intake of BHEI-R solid fats, alcoholic beverages and added sugars (SoFAAS) component below the median ( P interaction < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, a cross-sectional study of 228 Brazilian participants from the Health Survey of São Paulo (HS-SP) ( 64 ) observed significant interactions between a GRS based on seven SNPs ( Table 1 ) and the Brazilian Healthy Eating Index Revised (BHEI-R) on the risk of dyslipidaemia. Participants with a higher GRS (5–8) had a lower odds ratio for dyslipidaemia with an intake of BHEI-R oil component above the median ( P interaction = 0.019); while those with a GRS > 9 had a lower odds ratio for dyslipidaemia with an intake of BHEI-R solid fats, alcoholic beverages and added sugars (SoFAAS) component below the median ( P interaction < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Another issue that could affect the results is the accuracy of the methods used to measure exposure variables such as dietary intake and physical activity ( 167 , 168 ). Some studies used 24-h recall questionnaires and self-reporting methods ( 64 , 77 , 81 , 112 , 144 , 158 ), which might have induced recall bias, inadequate estimations, daily variation bias, and over and underreporting of values ( 169 , 170 ). Measurement of dietary intake is a crucial part of gene-diet interaction studies as under or overestimation of dietary intake can weaken or reverse the association between dietary factors and cardiometabolic traits ( 170 , 171 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence has suggested that the genetic risk of metabolic diseases can be modified by dietary intake [33][34][35][36][37]. There are a few genediet interaction studies in Brazilians; however, the studies have focused only on cardiovascular disease related traits [38][39][40]. To date, there are no GRS-diet interaction studies on metabolic traits in Brazilians.…”
Section: Introductionmentioning
confidence: 99%